Toward Chirality‐Encoded Domain Wall Logic. (22nd January 2019) - Omari, Khalid A.; Broomhall, Thomas J.; Dawidek, Richard W. S.; Allwood, Dan A.; Bradley, Ruth C.; Wood, Jonathan M.; Fry, Paul W.; Rosamond, Mark C.; Linfield, Edmund H.; Im, Mi‐Young; Fischer, Peter J.; Hayward, Tom J.
Abstract: Nonvolatile logic networks based on spintronic and nanomagnetic technologies have the potential to create high‐speed, ultralow power computational architectures. This article explores the feasibility of "chirality‐encoded domain wall logic, " a nanomagnetic logic architecture where data are encoded by the chiral structures of mobile domain walls in networks of ferromagnetic nanowires and processed by the chiral structures' interactions with geometric features of the networks. High‐resolution magnetic imaging is used to test two critical functionalities: the inversion of domain wall chirality at tailored artificial defect sites (logical NOT gates) and the chirality‐selective output of domain walls from 2‐in‐1‐out nanowire junctions (common operation to AND/NAND/OR/NOR gates). The measurements demonstrate both operations can be performed to a good degree of fidelity even in the presence of complex magnetization dynamics that would normally be expected to destroy chirality‐encoded information. Together, these results represent a strong indication of the feasibility of devices where chiral magnetization textures are used to directly carry, rather than merely delineate, data. Abstract : Magnetic logic devices where data are encoded within the winding of chiral domain walls are proposed. High‐resolution magnetic imaging techniques are used to show the feasibility of the NOT, AND, NAND, OR, and NOR gates. The work lays the ground for new forms of magnetic devices where domain walls are used to carry, rather than merely delineate information.